Nutritional status and morbidity among deaf-mute children attending special school in Nandyal, Andhra Pradesh: a cross sectional study - V., Bhargav; Pasha, M. A. Mushtaq; Fatima, Afsar (International Journal Of Community Medicine And Public Health, 2024)
Background: Deaf-mute children are those who have a hearing loss that prevents them from acquiring or using spoken language. They may use sign language, gestures, lip-reading, writing or other forms of communication. Hearing loss affects the quality of life and well-being of individuals, families and communities. According to WHO 63 million population in India with hearing loss, in that 4.5 million people are children under 15 years of age. Methods: A school based, cross-sectional study, done in Special school for deaf-mute, Nandyal over a period of June-July 2023 (2months) by using pre-designed, pre-tested, semi-structured questionnaire by interview method, with help of Convenience sampling technique for sample size of 100. A pre-designed semi-structured questionnaire was used to interview subjects after taking permission from the principal and confidentiality was ensured. The collected data were analysed using MS Excel and SPSS 2027 version. Results: Among 100 deaf-mute children, 57 were boys and 43 were girls, prevalence of undernutrition out of 57 boys were 49(85%) and among 43 girls were 27 (62%), overall prevalence of undernutrition were 76%, morbidity pattern showed that dental carries were second most common morbidity which were around 47%, followed by refractory error 12%. Conclusions: Understanding the interplay between deafness, muteness, and nutritional health is crucial for developing comprehensive care strategies. It is essential to address these challenges holistically, considering the socio-economic factors that influence access to nutritious food and healthcare services.